2021
DOI: 10.3389/fimmu.2021.666231
|View full text |Cite
|
Sign up to set email alerts
|

Optical Control of CD8+ T Cell Metabolism and Effector Functions

Abstract: Although cancer immunotherapy is effective against hematological malignancies, it is less effective against solid tumors due in part to significant metabolic challenges present in the tumor microenvironment (TME), where infiltrated CD8+ T cells face fierce competition with cancer cells for limited nutrients. Strong metabolic suppression in the TME is often associated with impaired T cell recruitment to the tumor site and hyporesponsive effector function via T cell exhaustion. Increasing evidence suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 57 publications
(76 reference statements)
2
18
0
Order By: Relevance
“…Since the advent of optogenetics, many top medical journals have described it as a core technology for the future of humanity ( Method of the year, 2010 ; News, 2010 ; Adamantidis et al, 2015 ). Optogenetics can be combined with molecular biology, viral biology and other methods to introduce foreign light-sensitive protein genes into living cells ( Amitrano et al, 2021 ; Di Ventura and Weber, 2021 ). Therefore, optogenetics has made many achievements in the field of neurobiology.…”
Section: Introductionmentioning
confidence: 99%
“…Since the advent of optogenetics, many top medical journals have described it as a core technology for the future of humanity ( Method of the year, 2010 ; News, 2010 ; Adamantidis et al, 2015 ). Optogenetics can be combined with molecular biology, viral biology and other methods to introduce foreign light-sensitive protein genes into living cells ( Amitrano et al, 2021 ; Di Ventura and Weber, 2021 ). Therefore, optogenetics has made many achievements in the field of neurobiology.…”
Section: Introductionmentioning
confidence: 99%
“…Recent study showed that G6PD is essential for mitochondrial function 33 and mitochondrial metabolic pathway regulates Gzmb expression in T cells. 34 It is known that the PPP metabolic pathway enhances mitochondrial acetyl-CoA production. 35 Analysis of genome-wide H3K9ac ChIP-Seq dataset in human T cells identified H3K9ac deposition at the GZMB promoter ( figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Amitrano et al set up a novel optogenetic approach based on light stimulation to specifically and remotely control T-cell OXPHOS. The authors were able to increase mitochondrial efficiency and ATP production in T cells, this having a positive effect on effector functions, including in vitro migration [ 127 ]. However, the application of this strategy in cancer immunotherapy requires further studies.…”
Section: Restoring Defective Car T Cell Migration By Targeting Immune...mentioning
confidence: 99%